2020
DOI: 10.1021/acs.macromol.0c00577
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation Behavior in Tough and Self-Healing Polyampholyte Hydrogels

Abstract: Polyampholyte hydrogels (PA gels) are drawing great attention for their excellent mechanical properties including self-healing, high toughness and fatigue resistance.These mechanical performances are found to be attributed to the hierarchical structure of the PA gels, consisting of reversible ionic bonds at the 1 nm scale, permanent polymer network at the 10 nm scale, and bicontinuous phase network at the hundred nm scale. In this work, we systematically studied the phase network formation of these gels, aimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 42 publications
1
79
0
Order By: Relevance
“…Our previous study showed that the level of phase contrast and characteristic phase length (d 0 ) of PA gels depend on the effective chain density of permanent polymer network  e and temperature (T dial ) used to dialyze the small counterions from the gels during the sample preparation (24,25).  e is due to the presence of chemical cross-links and trapped topological entanglements.…”
Section: Tuning the Mesoscale Phase Contrastmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that the level of phase contrast and characteristic phase length (d 0 ) of PA gels depend on the effective chain density of permanent polymer network  e and temperature (T dial ) used to dialyze the small counterions from the gels during the sample preparation (24,25).  e is due to the presence of chemical cross-links and trapped topological entanglements.…”
Section: Tuning the Mesoscale Phase Contrastmentioning
confidence: 99%
“…Accordingly, tuning the monomer concentration C m at the gel synthesis step can change the polymer concentration and thereby the concentration of the trapped topological entanglements. In this work, we vary the chemical cross-linker density (C MBAA ) to tune chemical cross-linking density and the total monomer concentration (C m ) to tune the topological entanglement density (24,28). Two series of samples were prepared by one-step random copolymerization of the anionic monomer sodium p-styrenesulfonate (NaSS) and the cationic monomer methyl chloride quarternized N,N-dimethylamino ethylacrylate (DMAEA-Q).…”
Section: Tuning the Mesoscale Phase Contrastmentioning
confidence: 99%
See 3 more Smart Citations